Developmental bias, macroevolution, and the fossil record. Issue 1 (11th September 2019) - Jablonski, David
Abstract: A fuller understanding of the role of developmental bias in shaping large‐scale evolutionary patterns requires integrating bias (the probability distribution of variation accessible to an ancestral phenotype) with clade dynamics (the differential survival and production of species and evolutionary lineages). This synthesis could proceed as a two‐way exchange between the developmental data available to neontologists and the strictly phenotypic but richly historical and dynamic data available to paleontologists. Analyses starting in extant populations could aim to predict macroevolution in the fossil record from observed developmental bias, while analyses starting in the fossil record, particularly the record of extant species and lineages, could aim to predict developmental bias from macroevolutionary patterns, including the broad range of extinct phenotypes. Analyses in multivariate morphospaces are especially effective when coupled with phylogeny, theoretical and developmental models, and diversity–disparity plots. This research program will also require assessing the "heritability" of an ancestral bias across phylogeny, and the tendency for bias change in strength and orientation over evolutionary time. Such analyses will help find a set of general rules for the macroevolutionary effects of developmental bias, including its impact on and interactions with the other intrinsic and extrinsic factors governing the movement, expansion, and contraction of clades in morphospace. Abstract : Many hypotheses have been framed the evolution of developmental bias within clades, and their macroevolutionary consequences. Here, developmental bias is visualized in two dimensions, with the bias having a volume, direction and eccentricity in morphospace, often proxied for living or fossil adult samples by within‐population variation, and expected to influence potential evolutionary trajectories from each successive starting point. For example, as shown here clades might begin with relatively isotropic variation, with evolutionary directions being similarly variable, but evolve stronger developmental bias through time, altering the most probable directions of evolutionary change. HIGHLIGHTS: A fuller, more synthetic understanding of the macroevolutionary role of developmental bias requires the integration of bias with clade dynamics—that is, the differential survival and production of species and evolutionary lineages